Doping in sport: a defence - Petersen, Thomas Søbirk (Routledge focus on sport, culture and society, 2020)
Warm up : the tunnel vision of the doping debate -- Doping and health -- Doping and the spirit of sport -- Doping and role models -- Doping and coercion -- Doping and the wish for a doping-free sport -- Doping and fair competition -- Doping and onwards : a run-off heat from the 4th division.